Irrigation Scheduling Based on Soil Moisture Sensors and Evapotranspiration - J. Aguilar; D. Rogers; I. Kisekka (Kansas Agricultural Experiment Station Research Reports, 2015)
Irrigation scheduling is crucial to effectively manage water resources and optimize profitability of an irrigated operation. Tools that can be customized to a field’s characteristics can greatly facilitate irrigation scheduling decisions. Soil moisture sensors and the evapotranspiration (ET)-based KanSched are two of the tools that could be implemented in an irrigated farm. Focusing on the installation of soil moisture sensors, demonstration set-ups were established at the Southwest Research-Extension Center plots in Garden City, Kansas, and in a producer’s field, each with three types of moisture sensors at different depths. Among others, this project validates the importance of moisture sensors being installed as early as possible in a representative location with good soil-sensor contact. The moisture sensors, at the least, help in determining when irrigation water should be applied or scheduled. Furthermore, in implementing an irrigation schedule, the irrigation manager considers the irrigation system capacity, the amount that can be efficiently applied, the soil intake rate, and other relevant factors.
Keywords: irrigation scheduling; irrigation frequency; water stress; moisture sensor; KanSched; water supply; soil water